A Multiple-Choice Bioassay Approach for Rapid Screening of Key Attractant Volatiles. Issue 4 (13th April 2018) - Cha, Dong H; Loeb, Gregory M; Linn, Charles E; Hesler, Stephen P; Landolt, Peter J
Abstract: Fermentation volatiles attract a wide variety of insects and are used for integrated pest management. However, identification of the key behavior modifying chemicals has often been challenging due to the time consuming nature of thorough behavioral tests and unexpected discrepancies between laboratory and field results. Thus we report on a multiple-choice bioassay approach that may expedite the process of identifying field-worthy attractants in the laboratory. We revisited the four-component key chemical blend (acetic acid, ethanol, acetoin, and methionol) identified from 12 antennally active wine and vinegar chemicals for Drosophila suzukii (Matsumura) (Diptera: Drosophilidae). The identification of this blend took 2 yr of continuous laboratory two-choice assays and then similarly designed field trials. This delay was mainly due to a discrepancy between laboratory and field results that laboratory two-choice assay failed to identify methionol as an attractant component. Using a multiple-choice approach, we compared the co-attractiveness of the 12 potential attractants to an acetic acid plus ethanol mixture, known as the basal attractant for D. suzukii, and found similar results as the previous field trials. Only two compounds, acetoin and, importantly, methionol, increased attraction to a mixture of acetic acid and ethanol, suggesting the identification of the four-component blend could have been expedited. Interestingly, the co-attractiveness of some of the 12 individual compounds, including a key attractant, methionol, appears to change when they were tested under different background odor environments, suggesting that background odor can influence detection of potential attractants. Our findings provide a potentially useful approach to efficiently identify behaviorally bioactive fermentation chemicals.